Hormonal and inflammatory responses to different types of sprint interval training - Meckel, Y.; Nemet, D.; Bar-Sela, S.; Radom-Aizik, S.; Cooper, D. M.; Sagiv, M.; Eliakim, A. (The Journal of Strength and Conditioning Research, 2011)
We evaluated the effect of different types of sprint interval sessions on the balance between anabolic and catabolic hormones and circulating inflammatory cytokines. Twelve healthy elite junior handball players (17-25 years) participated in the study. Exercise consisted of increasing distance (100 m, 200 m, 300 m, 400 m) and decreasing distance (400 m, 300 m, 200 m, 100 m) sprint interval runs on a treadmill (at random order), at a constant work rate of 80% of the personal maximal speed (calculated from the maximal speed of a 100 m run). The total rest period between the runs in the different interval sessions were similar. Blood samples were collected before, after each run, and after 1-hour recovery. Both types of sprint interval trainings led to a significant (p < 0.05) increase in lactate and the anabolic factors growth hormone, insulin-like growth factor-I (IGF-I), IGF binding protein-3 (IGFBP-3), and testosterone levels. Both types of sprint interval sessions led to a significant (p < 0.05) increase in the circulating pro- and anti-inflammatory mediators IL-1, IL-6, and IL1ra. IL-6 remained elevated in both sessions after 1-hour recovery. Area under the curve was significantly greater (p < 0.05) for lactate and growth hormone (GH) in the decreasing distance session. In contrast, rate of perceived exertion was higher in the increasing distance session, but this difference was not statistically significant (p = 0.07). Changes in anabolic-catabolic hormones and inflammatory mediators can be used to gauge the training intensity of anaerobic-type exercise. Changes in the GH-IGF-I axis and testosterone level suggest exercise-related anabolic adaptations. Increases in inflammatory mediators may indicate their important role in muscle tissue repair after anaerobic exercise. The decreasing distance interval was associated with a greater metabolic (lactate) and anabolic (GH) response but not with a higher rate of perceived exertion. Coaches and athletes should be aware of these differences, and as a result, of a need for specific recovery adaptations after different interval training protocols.